Burkitt's Lymphoma in a Pregnant Woman: Case Report and Review of the Literature. (9th May 2013) - Zagalo, Carlos; Pierdomenico, Francesca; Cabeçadas, José; David Santos, Pedro
Abstract : Burkitt's lymphoma (BL) is an aggressive B-cell malignancy with very high proliferation rate, more common in males than females. Here, we describe a case of Burkitt's lymphoma in a 24-week pregnant woman with cervical and abdominal involvement. The common genetic event of virtually all BL is a reciprocal chromosomal translocation involving the proto-oncogene MYC and one of the Ig gene heavy or light chain loci. Supportive treatment was administered until early delivery, after which the patient was treated according to protocol LMB96. Pregnancy and tumorogenesis share some important events such as immunologic tolerance, angiogenesis, and editing the host immune response. Little is known about the relationship between these events in pregnancy and in tumorogenesis.